CN103924752B - Nano wearproof pottery composite protective construction method - Google Patents

Nano wearproof pottery composite protective construction method Download PDF

Info

Publication number
CN103924752B
CN103924752B CN201410169540.2A CN201410169540A CN103924752B CN 103924752 B CN103924752 B CN 103924752B CN 201410169540 A CN201410169540 A CN 201410169540A CN 103924752 B CN103924752 B CN 103924752B
Authority
CN
China
Prior art keywords
construction
ceramic coating
nano
nano wearproof
wear
Prior art date
Legal status (The legal status is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the status listed.)
Expired - Fee Related
Application number
CN201410169540.2A
Other languages
Chinese (zh)
Other versions
CN103924752A (en
Inventor
焦丙军
宋志斌
吴生慧
Current Assignee (The listed assignees may be inaccurate. Google has not performed a legal analysis and makes no representation or warranty as to the accuracy of the list.)
JIAOZUO ANTAI WEARESIST TECHNOLOGY Co Ltd
Original Assignee
JIAOZUO ANTAI WEARESIST TECHNOLOGY Co Ltd
Priority date (The priority date is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the date listed.)
Filing date
Publication date
Application filed by JIAOZUO ANTAI WEARESIST TECHNOLOGY Co Ltd filed Critical JIAOZUO ANTAI WEARESIST TECHNOLOGY Co Ltd
Priority to CN201410169540.2A priority Critical patent/CN103924752B/en
Publication of CN103924752A publication Critical patent/CN103924752A/en
Application granted granted Critical
Publication of CN103924752B publication Critical patent/CN103924752B/en
Expired - Fee Related legal-status Critical Current
Anticipated expiration legal-status Critical

Links

Landscapes

  • Aftertreatments Of Artificial And Natural Stones (AREA)

Abstract

本发明公开了一种纳米耐磨陶瓷质复合防护施工方法,包括清理及焊接锚固网、耐磨材料的混合与搅拌、及施工步骤,施工以较小范围开始涂抹,施工时,将纳米耐磨陶瓷涂料紧紧地压入钢板网下方,致密涂抹。本发明施工方便、维护容易、性价比高、坚固耐用、节能环保。The invention discloses a construction method of nano-wear-resistant ceramic composite protection, which includes cleaning and welding anchor nets, mixing and stirring of wear-resistant materials, and construction steps. The ceramic paint is pressed tightly under the expanded metal for a dense application. The invention has the advantages of convenient construction, easy maintenance, high cost performance, durability, energy saving and environmental protection.

Description

纳米耐磨陶瓷质复合防护施工方法Nano wear-resistant ceramic composite protective construction method

技术领域 technical field

本发明涉及一种纳米耐磨陶瓷质复合防护施工方法。 The invention relates to a nanometer wear-resistant ceramic compound protective construction method.

背景技术 Background technique

水泥、国防、钢铁、火电、石油、化工等行业中涉及到各种高、低温设备,这些设备关键耐磨处理层等重磨损部位的处理关涉到设备的安全运行,甚至决定着设备的使用寿命。因而需要采用适当的防护方法进行处理。 Cement, national defense, steel, thermal power, petroleum, chemical and other industries involve various high and low temperature equipment. The treatment of the key wear-resistant treatment layer and other heavy wear parts of these equipment is related to the safe operation of the equipment, and even determines the service life of the equipment. . Therefore, it is necessary to adopt appropriate protective measures to deal with it.

目前,电厂中的许多重要部件,如锅炉四管,风机叶片,煤粉管道弯头,汽轮机末级叶片等,因磨损、高温腐蚀及水蚀等而使其使用寿命大大缩短,严重影响着机组的安全运行,直接影响电力生产的经济效益。 At present, many important components in the power plant, such as boiler four tubes, fan blades, pulverized coal pipe elbows, steam turbine final stage blades, etc., have greatly shortened their service life due to wear, high temperature corrosion, and water erosion, which seriously affects the unit. Safe operation directly affects the economic benefits of power production.

国内解决该类问题的办法多为定期更换受损部件,工期长且投入大。随着工业用新材料的开发,特殊高性能材料已成为材料科学研究的新热点。陶瓷及金属陶瓷与常规金属材料相比,具有极高的耐高温、耐氧化和耐磨性能,在西方发达国家已获广泛应用,以它作为表面防护材料,可大大延长设备的使用寿命,对保证设备的安全经济使用具有重要意义。 Most of the domestic solutions to such problems are regular replacement of damaged parts, which requires a long construction period and a large investment. With the development of new materials for industrial use, special high-performance materials have become a new hotspot in material science research. Compared with conventional metal materials, ceramics and cermets have extremely high temperature resistance, oxidation resistance and wear resistance. They have been widely used in western developed countries. Using them as surface protection materials can greatly prolong the service life of equipment. It is of great significance to ensure the safe and economical use of equipment.

综上,现有的防护方法及其问题有: To sum up, the existing protection methods and their problems are as follows:

(1)耐磨合金钢:具有良好的耐磨性,但材料强度高,施工难度大,非标制作时浪费大,制作时容易变形,最容易从焊接处被腐蚀。 (1) Wear-resistant alloy steel: It has good wear resistance, but the material strength is high, the construction is difficult, the waste is large during non-standard production, it is easy to deform during production, and it is most likely to be corroded from the weld.

(2)不锈钢:低温具有耐腐蚀性,但是不耐高温,高温下易被腐蚀磨损。 (2) Stainless steel: It has corrosion resistance at low temperature, but it is not resistant to high temperature, and it is easy to be corroded and worn at high temperature.

(3)普通耐磨料:有一定的耐磨性,造价相对低,强度低(小于35Pa),易产生裂纹,不能起到很好的防护作用。 (3) Ordinary wear-resistant materials: have certain wear resistance, relatively low cost, low strength (less than 35Pa), are prone to cracks, and cannot play a good protective role.

(4)陶瓷片:耐磨性、防腐性良好,有缝隙,由于施工时需采用树脂粘贴,容易老化,容易松动被气流吹脱落,使用周期短。 (4) Ceramic sheet: Good wear resistance and anti-corrosion, there are gaps, because it needs to be pasted with resin during construction, it is easy to age, easy to loose and fall off by air flow, and the service life is short.

由此可见,火力发电行业设备的重磨损部位采用耐磨陶瓷片、耐磨钢等工艺,因风选磨蚀、冲击磨蚀等原因需要频繁停工检修,影响了设备的利用率。 It can be seen that the heavy wear parts of the equipment in the thermal power generation industry adopt wear-resistant ceramic sheets, wear-resistant steel and other processes, and frequent shutdowns for maintenance are required due to winnowing abrasion, impact abrasion, etc., which affects the utilization rate of the equipment.

因而,如何开发出一种施工方便、维护容易、性价比高、坚固耐用、节能环保的防护施工方法,是一项新的研究课题。 Therefore, how to develop a protective construction method with convenient construction, easy maintenance, high cost performance, durability, energy saving and environmental protection is a new research topic.

发明内容 Contents of the invention

本发明需要解决的技术问题就在于克服现有技术的缺陷,提供一种纳米耐磨陶瓷质复合防护施工方法,它施工方便、维护容易、性价比高、坚固耐用、节能环保。 The technical problem to be solved by the present invention is to overcome the defects of the prior art and provide a nano-wear-resistant ceramic composite protective construction method, which is convenient in construction, easy in maintenance, high in cost performance, durable, energy-saving and environmentally friendly.

为解决上述问题,本发明采用如下技术方案: In order to solve the above problems, the present invention adopts the following technical solutions:

本发明公开了一种纳米耐磨陶瓷质复合防护施工方法,所述施工方法包括下列步骤: The invention discloses a nano-wear-resistant ceramic composite protective construction method, which includes the following steps:

1)、清理及焊接锚固网: 1), cleaning and welding anchoring mesh:

对需要施工的表面,先清洗掉油污或小颗粒物质,然后用角向砂轮机和钢丝砂轮机将钢板表面的铁锈除尽;在材料施工前,用水将施工表面浸湿,不能留有水珠或水滴; For the surface that needs to be constructed, first clean off the oil or small particles, and then use an angle grinder and a wire grinder to remove all the rust on the surface of the steel plate; before the construction of the material, wet the construction surface with water without leaving any water droplets or water droplets;

以钢板网为锚固网,钢板网采用未经电镀和油漆的普通碳钢网,以点焊方式固定钢板网与钢筋;在施工面焊接钢筋和钢板网;钢板网和施工面之间的距离足以让耐磨材料完全包裹住网;确认钢板网皆已牢固的覆盖于所有施工面上; The steel mesh is used as the anchor mesh, and the steel mesh is made of ordinary carbon steel mesh without electroplating and painting, and the steel mesh and steel bars are fixed by spot welding; the steel bars and steel mesh are welded on the construction surface; the distance between the steel mesh and the construction surface is sufficient Let the wear-resistant material completely wrap the mesh; confirm that the steel mesh has been firmly covered on all construction surfaces;

2)、耐磨材料的混合与搅拌: 2) Mixing and stirring of wear-resistant materials:

将纳米耐磨陶瓷涂料倒入强制式搅拌机内,先预混均匀后,加入自来水充分搅拌,加完水后搅拌3-10分钟; Pour the nano wear-resistant ceramic coating into the forced mixer, pre-mix evenly, add tap water and stir thoroughly, and stir for 3-10 minutes after adding water;

搅拌后,按照物料总质量4-5%的加入量,向搅拌机中均匀缓慢的加入钢纤维,所加的钢纤维不能形成块状;加完钢纤维并持续搅拌5-6分钟; After stirring, add steel fibers into the mixer evenly and slowly according to the amount of 4-5% of the total mass of the material, and the added steel fibers cannot form lumps; after adding the steel fibers, continue stirring for 5-6 minutes;

3)、施工: 3) Construction:

施工以较小范围开始涂抹,施工时,将纳米耐磨陶瓷涂料紧紧地压入钢板网下方,致密涂抹,直接在施工面上使用抹刀或振动抹刀,使其更均匀和紧密;在表面凝固之前,每次涂抹时达到所要求之厚度,完工之后,可用镘刀将其表面抹平,洒些水润湿; The construction begins with a small area of application. During construction, the nano-abrasion-resistant ceramic coating is tightly pressed into the steel mesh, densely applied, and a spatula or a vibrating spatula is directly used on the construction surface to make it more uniform and compact; Before the surface solidifies, reach the required thickness each time you apply it. After finishing, use a trowel to smooth the surface and sprinkle some water to moisten it;

当涂抹一个大面积的区域时,将其分成小区域,采用带钢或角钢顺工作方向焊接,分段要带钢做锐角处理。 When smearing a large area, divide it into small areas, use strip steel or angle steel to weld along the working direction, and segment the strip steel for acute angle treatment.

其中分三个界面搅拌及施工: There are three interfaces for mixing and construction:

(1)、水平表面的施工: (1) Construction of horizontal surface:

纳米耐磨陶瓷涂料搅拌结束后在20分钟内使用,即纳米耐磨陶瓷涂料有很好的黏性及适宜的流动性,避免出现二次加水,以保证纳米耐磨陶瓷涂料的强度不被降低;根据需要涂抹的工作面的大小,将适量的纳米耐磨陶瓷涂料倒在部件上,然后用砂浆板倒在各端,涂抹到所需厚度;不时检查涂抹的厚度,确保厚度准确; The nano wear-resistant ceramic coating should be used within 20 minutes after stirring, that is, the nano wear-resistant ceramic coating has good viscosity and suitable fluidity, avoiding secondary water addition, so as to ensure that the strength of the nano wear-resistant ceramic coating will not be reduced ;According to the size of the working surface that needs to be applied, pour an appropriate amount of nano wear-resistant ceramic paint on the parts, and then pour it on each end with a mortar board, and apply it to the required thickness; check the thickness of the application from time to time to ensure that the thickness is accurate;

(2)、垂直表面的施工: (2) Construction of vertical surfaces:

纳米耐磨陶瓷涂料要求搅拌时间在20分钟以上,加水搅拌3分钟以上,直至获得合适的黏稠度,能够形成一个“湿球”;将搅拌好的纳米耐磨陶瓷涂料放在砂板上,把砂浆板放到锚固网的表面,把砂浆压入锚固网和部件之间的夹层内;向上推动砂浆板的同时,从一端到另一端快速移动砂浆板;使用这种方法,纳米耐磨陶瓷涂料更易于施工,不时检查材抹的厚度。 The nano-wear-resistant ceramic coating requires stirring time of more than 20 minutes, add water and stir for more than 3 minutes, until a suitable viscosity is obtained, and a "wet ball" can be formed; put the stirred nano-wear-resistant ceramic coating on the sand board, put The mortar board is placed on the surface of the anchoring net, and the mortar is pressed into the interlayer between the anchoring net and the component; while pushing the mortar board up, move the mortar board quickly from one end to the other; using this method, the nano wear-resistant ceramic coating Easier to apply, check the thickness of the material from time to time.

(3)、头顶表面的施工: (3) Construction of the top surface of the head:

在纳米耐磨陶瓷涂料用于头顶位置时,增加3分钟的搅拌时间以获得黏性更大的纳米耐磨陶瓷涂料,;将新搅拌的纳米耐磨陶瓷涂料放置在砂浆板上,向上把纳米耐磨陶瓷涂料压入锚固网内,把砂浆板移回到起始位置,然后从一端到另一端做重复的“之”字形运动;使用这方法,将容易把耐磨纳米耐磨陶瓷涂料压入施工部件和锚固网之间的夹层。在耐磨纳米耐磨陶瓷涂料还“湿”的时间里,确保已获得准确的施工厚度; When the nano wear-resistant ceramic coating is used in the overhead position, add 3 minutes of stirring time to obtain a more viscous nano wear-resistant ceramic coating; place the newly stirred nano wear-resistant ceramic coating on the mortar board, and put the nano Press the wear-resistant ceramic coating into the anchoring net, move the mortar board back to the starting position, and then do repeated "zigzag" movements from one end to the other; using this method, it will be easy to press the wear-resistant nano wear-resistant ceramic coating Into the interlayer between the construction components and the anchoring mesh. When the wear-resistant nano wear-resistant ceramic coating is still "wet", ensure that the accurate construction thickness has been obtained;

涂抹时不断检查纳米耐磨陶瓷涂料,确认纳米耐磨陶瓷涂料完全压入锚固网的后面;用泥刀刮开约10mm*10mm的材料,露出锚固网,检查是否有气袋,如果有气袋,在涂抹时在锚固网后面压入更多的纳米耐磨陶瓷涂料;检查完之后,在刮开的地方再次涂抹纳米耐磨陶瓷涂料,并且用砂浆板抹平;如果检查发现气袋漏气,则已涂抹上的纳米耐磨陶瓷涂料从部件上除去,丢弃不再使用,用新的纳米耐磨陶瓷涂料重新涂抹施工。 When smearing, constantly check the nano wear-resistant ceramic coating to confirm that the nano wear-resistant ceramic coating is completely pressed into the back of the anchoring net; use a trowel to scrape off the material of about 10mm*10mm to expose the anchoring net, check whether there is an air pocket, if there is an air pocket , Press in more nano-wear-resistant ceramic paint behind the anchoring net when smearing; after inspection, apply nano-wear-resistant ceramic paint again on the scraped place, and smooth it with a mortar board; if the inspection finds that the air bag is leaking , then the nano wear-resistant ceramic paint that has been applied is removed from the parts, discarded and no longer used, and reapplied with new nano wear-resistant ceramic paint for construction.

制备纳米耐磨陶瓷涂料原材料的质量份配比为:5mm-8mm电熔刚玉65-70份,100nm-300nm纳米陶瓷粉15-20份,铝酸盐水泥3-6份,SiO2微粉2-5份,活性a-Al2O3粉2-5份,复合高效分散剂0.2-1份,促晶剂1-3份; The mass ratio of raw materials for preparing nano wear-resistant ceramic coatings is: 65-70 parts of 5mm-8mm fused corundum, 15-20 parts of 100nm-300nm nano-ceramic powder, 3-6 parts of aluminate cement, 2- 5 parts, 2-5 parts of active a-Al 2 O 3 powder, 0.2-1 part of composite high-efficiency dispersant, 1-3 parts of crystal accelerator;

其中,制备纳米陶瓷粉的原料质量份配比为:氧化锆9-11份,氧化铝73-77份,氧化镁5-7份,氧化锌5-7份,氧化钴2-4; Wherein, the mass ratio of raw materials for preparing nano-ceramic powder is: 9-11 parts of zirconia, 73-77 parts of aluminum oxide, 5-7 parts of magnesium oxide, 5-7 parts of zinc oxide, and 2-4 parts of cobalt oxide;

所述复合高效分散剂为氨基磺酸系高效减水剂,所述促晶剂为镁的氧化物、氯化物等低温可发生、促进水化反应的物质。 The composite high-efficiency dispersant is a sulfamic acid-based high-efficiency water reducer, and the crystal accelerator is a substance that can occur at low temperature and promote hydration reaction such as magnesium oxide and chloride.

采用高温煅烧磨细法制备纳米陶瓷粉,将纳米陶瓷粉与电熔刚玉、铝酸盐水泥、SiO2微粉、活性a-Al2O3粉、复合高效分散剂和促晶剂一起配制成纳米耐磨陶瓷涂料。 Nano-ceramic powder is prepared by high-temperature calcining and grinding method, and nano-ceramic powder is prepared together with fused corundum, aluminate cement, SiO 2 micropowder, active a-Al 2 O 3 powder, composite high-efficiency dispersant and crystal accelerator. Wear-resistant ceramic coating.

施工温度要求为:施工期间,施工地点的气温控制在5℃-30℃,气温过低时,材料本身及施工区域加温至5℃以上,直到陶瓷料涂抹完毕为止;在高温时避免在直接日晒或强风状况下施工,防止材料表面的迅速干裂、削弱材料强度。 The construction temperature requirements are as follows: during the construction period, the temperature at the construction site should be controlled at 5°C-30°C. When the temperature is too low, the material itself and the construction area should be heated to above 5°C until the application of the ceramic material is completed; Construction under the sun or strong wind to prevent the surface of the material from drying out quickly and weakening the strength of the material.

清理及焊接锚固网时,为了防止施工面边缘变形和干裂,在施工面的边缘焊接厚5mm、高20mm扁铁,焊接角度与所在的工作面垂直。 When cleaning and welding the anchor net, in order to prevent deformation and dry cracking of the edge of the construction surface, a flat iron with a thickness of 5mm and a height of 20mm is welded on the edge of the construction surface, and the welding angle is perpendicular to the working surface where it is located.

施工注意事项为: Construction precautions are:

1)、纳米耐磨陶瓷涂料一定要紧紧的压入锚固网的下方。 1) The nano wear-resistant ceramic coating must be tightly pressed into the bottom of the anchoring net.

2)、施工区域必须清理干净,并按照以上所述执行。 2) The construction area must be cleaned up and implemented in accordance with the above.

3)、施工于水平面时,建议直接在覆盖面或镘刀上使用振动机,使其更加均匀和致密。但是在垂直面或向下面施工时,则不可使用振动机。 3) When constructing on a horizontal surface, it is recommended to use a vibrating machine directly on the covering surface or trowel to make it more uniform and dense. However, the vibrating machine cannot be used in vertical or downward construction.

4)、表面完成之后,必须立即保护表面以防止迅速干化,通常用一般喷雾器将养护剂喷洒于表面即可。每平方米约需喷洒0.2~0.3L的养护剂,也可洒水养护。在施工面边缘部位养护剂喷洒量需增加一倍,防止产生裂纹。 4) After the surface is finished, the surface must be protected immediately to prevent rapid drying. Usually, a general sprayer is used to spray the curing agent on the surface. About 0.2-0.3L of curing agent needs to be sprayed per square meter, and watering can also be used for curing. The amount of curing agent sprayed on the edge of the construction surface needs to be doubled to prevent cracks.

5)、施工完毕后的纳米耐磨陶瓷涂料尽可能达到7d的养护期,原则上至少不低于3d。在养护期内,必须每天进行养护。 5) After construction, the nano-wear-resistant ceramic coating should have a curing period of 7 days as much as possible, and in principle, at least not less than 3 days. During the maintenance period, maintenance must be carried out every day.

6)、纳米耐磨陶瓷涂料在施工过程中及养护期内,严禁任何敲打、锤击等冲击性行为。 6) During the construction and maintenance period of the nano wear-resistant ceramic coating, any impact behavior such as beating and hammering is strictly prohibited.

7)、耐磨纳米耐磨陶瓷涂料应该在初凝前施工完毕,一次搅拌量应根据初凝时间和施工所需要的材料边搅拌边用,失去和易性的耐磨涂料严禁二次加水搅拌再用。 7) The wear-resistant nano wear-resistant ceramic coating should be completed before the initial setting, and the amount of primary mixing should be used while stirring according to the initial setting time and the materials required for construction. The wear-resistant coating that has lost workability is strictly prohibited from adding water for the second time. use again.

本发明施工方便、维护容易、性价比高、坚固耐用、节能环保。 The invention has the advantages of convenient construction, easy maintenance, high cost performance, durability, energy saving and environmental protection.

具体实施方式 detailed description

制备纳米耐磨陶瓷涂料原材料的质量份配比为:5mm-8mm电熔刚玉65-70份,100nm-300nm纳米陶瓷粉15-20份,铝酸盐水泥3-6份,SiO2微粉2-5份,活性a-Al2O3粉2-5份,复合高效分散剂0.2-1份,促晶剂1-3份; The mass ratio of raw materials for preparing nano wear-resistant ceramic coatings is: 65-70 parts of 5mm-8mm fused corundum, 15-20 parts of 100nm-300nm nano-ceramic powder, 3-6 parts of aluminate cement, 2- 5 parts, 2-5 parts of active a-Al 2 O 3 powder, 0.2-1 part of composite high-efficiency dispersant, 1-3 parts of crystal accelerator;

其中,制备纳米陶瓷粉的原料质量份配比为:氧化锆9-11份,氧化铝73-77份,氧化镁5-7份,氧化锌5-7份,氧化钴2-4; Wherein, the mass ratio of raw materials for preparing nano-ceramic powder is: 9-11 parts of zirconia, 73-77 parts of aluminum oxide, 5-7 parts of magnesium oxide, 5-7 parts of zinc oxide, and 2-4 parts of cobalt oxide;

所述复合高效分散剂为氨基磺酸系高效减水剂,所述促晶剂为镁的氧化物、氯化物等低温可发生、促进水化反应的物质。 The composite high-efficiency dispersant is a sulfamic acid-based high-efficiency water reducer, and the crystal accelerator is a substance that can occur at low temperature and promote hydration reaction such as magnesium oxide and chloride.

采用高温煅烧磨细法制备纳米陶瓷粉,将纳米陶瓷粉与电熔刚玉、铝酸盐水泥、SiO2微粉、活性a-Al2O3粉、复合高效分散剂和促晶剂一起配制成纳米耐磨陶瓷涂料。 Nano-ceramic powder is prepared by high-temperature calcining and grinding method, and nano-ceramic powder is prepared together with fused corundum, aluminate cement, SiO 2 micropowder, active a-Al 2 O 3 powder, composite high-efficiency dispersant and crystal accelerator. Wear-resistant ceramic coating.

1、施工前的准备1. Preparation before construction

1、检查所有施工人员的劳保穿戴是否齐全; 1. Check whether the labor protection clothing of all construction workers is complete;

2、检查施工所需工具和施工所需材料是否到位; 2. Check whether the tools and materials required for construction are in place;

3、检查适宜的温度及保证措施(详见温度要求)是否到位; 3. Check whether the appropriate temperature and guarantee measures (see temperature requirements for details) are in place;

4、由施工方负责人申请工程现场电气负责人检查我方配电柜并接通电源; 4. The person in charge of the construction party shall apply for the electrical person in charge of the project site to check our power distribution cabinet and connect the power supply;

2、施工温度要求:2. Construction temperature requirements:

施工期间,施工地点的气温须控制在5℃至30℃之间,如气温过低时,材料本身及施工区域则须加温至5℃以上,直到陶瓷料涂抹完毕为止。在高温时应避免在直接日晒或强风状况下施工,以防止材料表面的迅速干裂,削弱材料强度。 During the construction period, the temperature at the construction site must be controlled between 5°C and 30°C. If the temperature is too low, the material itself and the construction area must be heated to above 5°C until the ceramic material is applied. At high temperature, construction should be avoided under direct sunlight or strong wind, so as to prevent the surface of the material from drying out quickly and weakening the strength of the material.

3、施工3. Construction

3.1、清理及焊接锚固网3.1. Cleaning and welding anchoring mesh

对需要施工的表面,先清洗掉油污或小颗粒物质,然后用角向砂轮机和钢丝砂轮机将钢板表面的铁锈除尽。在材料施工前,用水将施工表面浸湿,但不能留有水珠或水滴。 For the surface that needs to be constructed, first clean off the oil or small particles, and then use an angle grinder and a wire grinder to remove the rust on the surface of the steel plate. Before the material is applied, the construction surface should be wetted with water, but no water beads or droplets should be left.

为了防止施工面边缘变形和干裂,可以在施工面的边缘焊接厚5mm,高20mm扁铁,焊接角度与所在的工作面垂直。 In order to prevent deformation and dry cracking of the edge of the construction surface, a flat iron with a thickness of 5mm and a height of 20mm can be welded on the edge of the construction surface, and the welding angle is perpendicular to the working surface where it is located.

在施工面焊接Φ6mm钢筋和钢板网,焊点间距为200-300mm。 Weld Φ6mm steel bars and steel mesh on the construction surface, and the welding spot spacing is 200-300mm.

确认钢板网皆已牢固的覆盖于所有施工面上。钢板补强网的作用旨在使已涂抹上的耐磨材料不致脱落,尤其是在垂直表面施工或施工面朝下时。钢板网需采用未经电镀和油漆的普通碳钢网。 Confirm that the expanded metal has been firmly covered on all construction surfaces. The role of the steel plate reinforcement mesh is to prevent the applied wear-resistant material from falling off, especially when it is applied on a vertical surface or the construction surface is facing downwards. The steel mesh needs to use ordinary carbon steel mesh without electroplating and painting.

备注:根据施工经验,建议使用未经电镀之补强网,其参考尺寸为33*88mm。 Remarks: According to construction experience, it is recommended to use non-plated reinforcing mesh, and its reference size is 33*88mm.

为了确保最强固的附着性,安装时应尽量调整补强网,使网和施工面之间的距离足以让耐磨材料完全包裹住网。锚固网与钢筋以点焊方式固定,一般点焊之间的间距为100-150mm。 In order to ensure the strongest adhesion, the reinforcing mesh should be adjusted as far as possible during installation, so that the distance between the mesh and the construction surface is sufficient for the wear-resistant material to completely wrap the mesh. The anchor net and the steel bar are fixed by spot welding, and the distance between the spot welding is generally 100-150mm.

3.2、耐磨材料的混合与搅拌3.2. Mixing and stirring of wear-resistant materials

将纳米耐磨陶瓷涂料倒入强制式搅拌机内,先预混均匀后,按适合配比规定,缓慢的加入清洁的自来水充分搅拌,加完水后搅拌3-5分钟。(在3分钟内耐磨料的外观会从干粉状变为湿润和粘稠状)。根据现场搅拌情况,如果纳米耐磨陶瓷涂料没有展现适合施工的粘稠状,可以再向搅拌机内补充适量的自来水,直至获得合适的粘稠度为止。每次额外加水后,再搅拌至少1分钟。加入钢纤维之前总的搅拌时间不得少于10分钟。 Pour the nano wear-resistant ceramic coating into the forced mixer, pre-mix evenly, then slowly add clean tap water and stir thoroughly according to the appropriate ratio, and stir for 3-5 minutes after adding water. (The appearance of the abrasive will change from dry powdery to wet and sticky within 3 minutes). According to the on-site mixing situation, if the nano wear-resistant ceramic coating does not show a viscous shape suitable for construction, you can add an appropriate amount of tap water to the mixer until a suitable viscosity is obtained. Stir for at least 1 minute after each additional addition of water. The total stirring time before adding the steel fibers shall not be less than 10 minutes.

如果粘稠度合适,搅拌10分钟后,按照4-5%的加入量,向搅拌机中均匀缓慢的加入钢纤维,所加的钢纤维不能形成块状。加完钢纤维并持续搅拌5-6分钟。 If the consistency is suitable, after stirring for 10 minutes, add steel fibers into the mixer evenly and slowly according to the amount of 4-5%, and the added steel fibers cannot form lumps. Finish adding the steel fiber and keep stirring for 5-6 minutes.

搅拌完成后,再次检查纳米耐磨陶瓷涂料的工作性。如果纳米耐磨陶瓷涂料能形成一个“湿球”,就表明有好的工作性,可以开始涂抹。 After the stirring is completed, check the workability of the nano wear-resistant ceramic coating again. If the nano wear-resistant ceramic coating can form a "wet ball", it shows that it has good workability and can be applied.

3.3、施工3.3. Construction

施工时,纳米耐磨陶瓷涂料一定要紧紧地压入钢板网下方。直接在施工面上使用抹刀或振动抹刀,使其更均匀和紧密。施工应以较小范围开始涂抹,并紧紧压至钢板网之下,更重要的是必须致密涂抹,在表面凝固之前,应该在每次涂抹时达到所要求之厚度,完工之后,可用镘刀将其表面抹平,必要时洒些水润湿。 During construction, the nano wear-resistant ceramic coating must be tightly pressed into the steel mesh. Use a trowel or vibrating trowel directly on the application surface for a more even and compact finish. The construction should start with a small area and press it tightly under the steel mesh. More importantly, it must be densely applied. Before the surface solidifies, it should reach the required thickness each time it is applied. After completion, you can use a trowel Smooth its surface and sprinkle some water to moisten it if necessary.

当涂抹一个大面积的区域时,有必要将其分成小区域,采用带钢或角钢顺工作风向焊接,分段要带钢做锐角处理。 When smearing a large area, it is necessary to divide it into small areas, and use strip steel or angle steel to weld along the working wind direction, and the section should be strip steel for acute angle treatment.

其中分三个界面搅拌及施工: There are three interfaces for mixing and construction:

(1)、水平表面的施工:(1) Construction of horizontal surface:

搅拌结束后应在20分钟内使用,即纳米耐磨陶瓷涂料有很好的黏性及适宜的流动性,水量要控制在最低标准,避免出现二次加水,以保证纳米耐磨陶瓷涂料的强度不被降低。根据需要涂抹的工作面的大小,将适量的纳米耐磨陶瓷涂料倒在部件上,然后用砂浆板倒在各端,涂抹到所需厚度。要不时检查涂抹的厚度,确保厚度准确。 It should be used within 20 minutes after stirring, that is, the nano-abrasion-resistant ceramic coating has good viscosity and suitable fluidity, and the amount of water should be controlled at the minimum standard to avoid secondary water addition to ensure the strength of the nano-abrasion-resistant ceramic coating is not lowered. According to the size of the working surface that needs to be painted, pour an appropriate amount of nano wear-resistant ceramic paint on the parts, and then pour it on each end with a mortar board, and apply it to the required thickness. Check the thickness of the application from time to time to ensure the thickness is correct.

(2)、垂直表面的施工:(2) Construction of vertical surfaces:

要求搅拌时间在20分钟以上(取决于气候条件)加水搅拌3分钟以上,直至获得合适的黏稠度(能够形成一个“湿球”)。将搅拌好的纳米耐磨陶瓷涂料放在砂板上,把砂浆板放到锚固网的表面,把砂浆压入锚固网和部件之间的夹层内。向上推动砂浆板的同时,从一端到另一端快速移动砂浆板。使用这种方法,纳米耐磨陶瓷涂料更易于施工,不时检查材抹的厚度。 Stirring time is required to be more than 20 minutes (depending on the weather conditions), add water and stir for more than 3 minutes until a suitable consistency is obtained (a "wet ball" can be formed). Put the stirred nano wear-resistant ceramic coating on the sand board, put the mortar board on the surface of the anchor net, and press the mortar into the interlayer between the anchor net and the components. While pushing the mortar board up, move the mortar board quickly from one end to the other. Using this method, the nano wear-resistant ceramic coating is easier to apply, and the thickness of the material should be checked from time to time.

(3)、头顶表面的施工:(3) Construction of the top surface of the head:

在纳米耐磨陶瓷涂料用于头顶位置时,增加3分钟的搅拌时间以获得黏性更大的纳米耐磨陶瓷涂料,将会有利于顶部的施工。 When the nano-abrasion-resistant ceramic coating is used on the top of the head, adding 3 minutes of stirring time to obtain a more viscous nano-abrasion-resistant ceramic coating will be conducive to the construction of the top.

将新搅拌的纳米耐磨陶瓷涂料放置在砂浆板上,向上把纳米耐磨陶瓷涂料压入锚固网内,把砂浆板移回到起始位置,然后从一端到另一端做重复的“之”字形运动。使用这方法,将容易把耐磨纳米耐磨陶瓷涂料压入施工部件和锚固网之间的夹层。在耐磨纳米耐磨陶瓷涂料还“湿”的时间里,确保已获得准确的施工厚度。 Place the newly stirred nano-abrasion-resistant ceramic coating on the mortar board, press the nano-abrasion-resistant ceramic coating upwards into the anchoring mesh, move the mortar board back to the starting position, and then do a repeated "this" from one end to the other glyph movement. Using this method, it will be easy to press the wear-resistant nano wear-resistant ceramic coating into the interlayer between the construction parts and the anchoring net. During the time that the wear-resistant nano wear-resistant ceramic coating is still "wet", ensure that the accurate application thickness has been obtained.

为确保施工的工程质量,施工人员必须站在尽量靠近头顶施工的地方,必要时还需低头施工。这样施工人员才有足够的力量下压和移动砂浆板。 In order to ensure the engineering quality of the construction, the construction personnel must stand as close to the top of the head as possible, and bow their heads when necessary. In this way, the construction personnel have enough strength to press down and move the mortar board.

涂抹时不断检查安泰耐磨纳米耐磨陶瓷涂料,确认纳米耐磨陶瓷涂料完全压入锚固网的后面。用泥刀刮开约10mm*10mm的材料,露出锚固网,检查是否有气袋,如果有气袋,在涂抹时应该在锚固网后面压入更多的纳米耐磨陶瓷涂料。检查完之后,在刮开的地方再次涂抹纳米耐磨陶瓷涂料,并且用砂浆板抹平。如果检查发现气袋漏气,则已涂抹上的纳米耐磨陶瓷涂料应该从部件上除去,丢弃不再使用,必须用新的纳米耐磨陶瓷涂料重新涂抹施工。 Constantly check the Aetna wear-resistant nano-abrasion-resistant ceramic coating when applying it, and confirm that the nano-abrasion-resistant ceramic coating is completely pressed into the back of the anchoring mesh. Use a trowel to scrape off the material of about 10mm*10mm to expose the anchoring mesh, and check whether there are air pockets. If there are air pockets, press more nano-wear-resistant ceramic coatings behind the anchoring mesh when applying. After the inspection, apply the nano wear-resistant ceramic coating again on the scratched place, and smooth it with a mortar board. If the inspection finds that the air bag is leaking, the applied nano-abrasion-resistant ceramic coating should be removed from the part, discarded and no longer used, and must be reapplied with a new nano-abrasion-resistant ceramic coating.

3.4、施工注意事项3.4. Construction precautions

3.4.1、纳米耐磨陶瓷涂料一定要紧紧的压入锚固网的下方。 3.4.1. The nano wear-resistant ceramic coating must be tightly pressed into the bottom of the anchoring net.

3.4.2、施工区域必须清理干净,并按照以上所述执行。 3.4.2 . The construction area must be cleaned up and implemented in accordance with the above.

3.4.3、施工于水平面时,建议直接在覆盖面或镘刀上使用振动机,使其更加均匀和致密。但是在垂直面或向下面施工时,则不可使用振动机。 3.4.3 When constructing on a horizontal surface, it is recommended to use a vibrating machine directly on the covering surface or a trowel to make it more uniform and compact. However, the vibrating machine cannot be used in vertical or downward construction.

3.4.4、表面完成之后,必须立即保护表面以防止迅速干化,通常用一般喷雾器将养护剂喷洒于表面即可。每平方米约需喷洒0.2~0.3L的养护剂,也可洒水养护。在施工面边缘部位养护剂喷洒量需增加一倍,防止产生裂纹。 3.4.4 After the surface is finished, the surface must be protected immediately to prevent rapid drying. Usually, it is enough to spray the curing agent on the surface with a general sprayer. About 0.2-0.3L of curing agent needs to be sprayed per square meter, and watering can also be used for curing. The amount of curing agent sprayed on the edge of the construction surface needs to be doubled to prevent cracks.

3.4.5、施工完毕后的纳米耐磨陶瓷涂料尽可能达到7d的养护期,原则上至少不低于3d。在养护期内,必须每天进行养护。 3.4.5 . After the construction is completed, the nano-abrasion-resistant ceramic coating should have a curing period of 7 days as far as possible, and in principle it should not be less than 3 days. During the maintenance period, maintenance must be carried out every day.

3.4.6、纳米耐磨陶瓷涂料在施工过程中及养护期内,严禁任何敲打、锤击等冲击性行为。 3.4.6. During the construction and maintenance period of the nano wear-resistant ceramic coating, any impact behavior such as beating and hammering is strictly prohibited.

3.4.7、耐磨纳米耐磨陶瓷涂料应该在初凝前施工完毕,一次搅拌量应根据初凝时间和施工所需要的材料边搅拌边用,失去和易性的耐磨涂料严禁二次加水搅拌再用。 3.4.7 The wear-resistant nano wear-resistant ceramic coating should be completed before the initial setting. The amount of primary mixing should be used while stirring according to the initial setting time and the materials required for construction. The wear-resistant coating that loses workability is strictly prohibited from adding water twice Stir again.

制备纳米耐磨陶瓷涂料原材料的质量份配比为:5mm-8mm电熔刚玉65-70份,100nm-300nm纳米陶瓷粉15-20份,铝酸盐水泥3-6份,SiO2微粉2-5份,活性a-Al2O3粉2-5份,复合高效分散剂0.2-1份,促晶剂1-3份; The mass ratio of raw materials for preparing nano wear-resistant ceramic coatings is: 65-70 parts of 5mm-8mm fused corundum, 15-20 parts of 100nm-300nm nano-ceramic powder, 3-6 parts of aluminate cement, 2- 5 parts, 2-5 parts of active a-Al 2 O 3 powder, 0.2-1 part of composite high-efficiency dispersant, 1-3 parts of crystal accelerator;

其中,制备纳米陶瓷粉的原料质量份配比为:氧化锆9-11份,氧化铝73-77份,氧化镁5-7份,氧化锌5-7份,氧化钴2-4; Wherein, the mass ratio of raw materials for preparing nano-ceramic powder is: 9-11 parts of zirconia, 73-77 parts of aluminum oxide, 5-7 parts of magnesium oxide, 5-7 parts of zinc oxide, and 2-4 parts of cobalt oxide;

所述复合高效分散剂为氨基磺酸系高效减水剂,所述促晶剂为镁的氧化物、氯化物等低温可发生、促进水化反应的物质 The composite high-efficiency dispersant is a sulfamic acid-based high-efficiency water reducer, and the crystal accelerator is a substance that can occur at low temperatures and promote hydration reactions such as magnesium oxides and chlorides

采用高温煅烧磨细法制备纳米陶瓷粉,将纳米陶瓷粉与电熔刚玉、铝酸盐水泥、SiO2微粉、活性a-Al2O3粉、复合高效分散剂和促晶剂一起配制成纳米耐磨陶瓷涂料。 Nano-ceramic powder is prepared by high-temperature calcining and grinding method, and nano-ceramic powder is prepared together with fused corundum, aluminate cement, SiO 2 micropowder, active a-Al 2 O 3 powder, composite high-efficiency dispersant and crystal accelerator. Wear-resistant ceramic coating.

最后应说明的是:显然,上述实施例仅仅是为清楚地说明本发明所作的举例,而并非对实施方式的限定。对于所属领域的普通技术人员来说,在上述说明的基础上还可以做出其它不同形式的变化或变动。这里无需也无法对所有的实施方式予以穷举。而由此所引申出的显而易见的变化或变动仍处于本发明的保护范围之中。 Finally, it should be noted that: obviously, the above-mentioned embodiments are only examples for clearly illustrating the present invention, rather than limiting the implementation. For those of ordinary skill in the art, other changes or changes in different forms can be made on the basis of the above description. It is not necessary and impossible to exhaustively list all the implementation manners here. However, the obvious changes or variations derived therefrom are still within the protection scope of the present invention.

Claims (5)

1. a nano wearproof pottery composite protective construction method, is characterized in that, described construction method comprises the following steps:
1), cleaning and weld anchor fixed network:
To the surface needing construction, first wash greasy dirt or finely ground particle substance, then with electric angle grinder and steel-wire sanding wheel machine, the iron rust of surface of steel plate is eliminated; Before material construction, will to construct surface wet with water, the globule or water droplet can not be left;
Take expanded metal lath as anchored net, expanded metal lath adopts the ordinary carbon steel net without plating and paint, with spot welding mode fixation steel plate net and reinforcing bar; At working face welded reinforcement and expanded metal lath; Distance between expanded metal lath and working face is enough to allow high-abrasive material wrap net completely; Confirm that expanded metal lath is all firmly covered in all working face;
2), the mixing of high-abrasive material and stirring:
Nano wearproof ceramic coating is poured in forced mixer, after first premix is even, adds tap water and fully stir, after water injection stir 3-10 minute afterwards;
After stirring, according to the addition of material gross mass 4-5%, in mixer, evenly add steel fibre slowly, added steel fibre can not form bulk; Add steel fibre and Keep agitation 5-6 minute;
3), construct:
Construction is to start more among a small circle to smear, and during construction, be pressed into tightly below expanded metal lath by nano wearproof ceramic coating, densification is smeared, and directly in working face, uses spatula, makes it evenly with tight; Before surface solidification, when smearing, reach required thickness at every turn, after completion, with trowel by floating for its surface, spill a little water-wet;
When smearing a large-area region, be divided into zonule;
Three kinds of interfaces are divided to stir and construction:
(1), the construction of horizontal surface:
Nano wearproof ceramic coating used after stirring and terminating in 20 minutes, and namely nano wearproof ceramic coating has good stickiness and suitable mobility, avoids occurring that secondary adds water, to ensure that the intensity of nano wearproof ceramic coating is not lowered; The size of the work plane smeared as required, is poured on parts by appropriate nano wearproof ceramic coating, is then poured on each end with Mortar Plates, is applied to desired thickness; Frequently check the thickness smeared, guarantee that thickness is accurate;
(2), the construction of vertical surface:
Nano wearproof ceramic coating requires that mixing time is more than 20 minutes, and add water stirring more than 3 minutes, until obtain suitable stickiness, can be formed one " wet bulb "; The nano wearproof ceramic coating be stirred is placed on sand plate, Mortar Plates is put into the surface of anchored net, in the interlayer between mortar press-in anchored net and parts; Upwardly while Mortar Plates, pass through quick mobile Mortar Plates; Make in this way, nano wearproof ceramic coating is easier to construction, frequently checks the thickness that material is smeared;
(3), the construction on surface, the crown:
When nano wearproof ceramic coating is used for position, the crown, increase the mixing time of 3 minutes to obtain the larger nano wearproof ceramic coating of stickiness; Be placed on Mortar Plates by the nano wearproof ceramic coating newly stirred, upwards in nano wearproof ceramic coating press-in anchored net, Mortar Plates be moved back into original position, then pass through the "the" shape motion doing repetition; Use this method, easily nano wearproof ceramic coating will be pressed into the interlayer between construction parts and anchored net; In the time that nano wearproof ceramic coating also " wets ", guarantee to obtain thickness of constructing accurately;
Constantly check nano wearproof ceramic coating when smearing, confirm that nano wearproof ceramic coating is pressed into after anchored net completely; Scraping the material of 10mm*10mm with trowel off, expose anchored net, checked whether airbag, if there is airbag, after anchored net, being pressed into more nano wearproof ceramic coating when smearing; After checking out, again smear nano wearproof ceramic coating in the place scraped off, and floating with Mortar Plates; If check and find airbag gas leakage, be then coated with the nano wearproof ceramic coating spread and removed from parts, abandoned and do not re-use, again smeared construction with new nano wearproof ceramic coating.
2. nano wearproof pottery composite protective construction method as claimed in claim 1, it is characterized in that, preparing the raw-material proportion by weight of nano wearproof ceramic coating is: 5mm-8mm electro-corundum 65-70 part, 100nm-300nm nano-ceramic powder 15-20 part, aluminate cement 3-6 part, SiO 2micro mist 2-5 part, active a-Al 2o 3powder 2-5 part, composite highly effective dispersing agent 0.2-1 part, crystallization-promoter 1-3 part;
Wherein, the material quality part proportioning preparing nano-ceramic powder is: zirconia 9-11 part, alumina 73-77 part, magnesia 5-7 part, zinc oxide 5-7 part, cobalt oxide 2-4 part;
Described composite highly effective dispersing agent is amido sulfoacid series high-efficiency water reducer, and described crystallization-promoter is oxide, the chloride of magnesium;
Adopt the levigate legal system of high-temperature calcination for nano-ceramic powder, by nano-ceramic powder and electro-corundum, aluminate cement, SiO 2micro mist, active a-Al 2o 3powder, composite highly effective dispersing agent are mixed with nano wearproof ceramic coating together with crystallization-promoter.
3. nano wearproof pottery composite protective construction method as claimed in claim 2, it is characterized in that, construction temperature requires: construction period, the temperature of job location controls at 5 DEG C-30 DEG C, when temperature is too low, material itself and construction area are heated to more than 5 DEG C, until ceramic material is smeared complete; Avoid when high temperature constructing under direct Exposure to Sunlight or high wind situation, prevent dry and cracked rapidly, the weakening strength of materials of material surface.
4. nano wearproof pottery composite protective construction method as claimed in claim 3, it is characterized in that, when cleaning and weld anchor fixed network, in order to prevent working face edge deformation and dry and cracked, weld thick 5mm, high 20mm band iron at the edge of working face, soldering angle is vertical with the work plane at place.
5. as claim 1-4 arbitrary as described in nano wearproof pottery composite protective construction method, it is characterized in that, construction precautions is:
1), nano wearproof ceramic coating must the below of press-in anchored net tightly;
2), construction area must be cleaned out, and perform according to the above;
3), construct when horizontal plane, suggestion directly uses bobbing machine on coverage rate or trowel, makes its more all even densification, but when vertical plane or downward surface construction, then can not use bobbing machine;
4), after surface completes, surface must be protected immediately to prevent rapid mummification, curing agent is sprayed on surface by the general sprayer of usual use, every square metre of curing agent that need spray 0.2 ~ 0.3L, also can to sprinkle water maintenance, in working face edge, curing agent fountain height need double, and prevents crackle;
5) the nano wearproof ceramic coating, after construction reaches the curing time of 7d as far as possible, is at least not less than 3d in principle, within curing time, must carries out maintenance every day;
6), nano wearproof ceramic coating is in work progress and in curing time, forbids anyly to beat, hammer impacts sexual behaviour;
7), nanometer antiwear wearable ceramic coat should construct complete before initial set, and amount of agitation should material use while stirring required for initial setting time and construction, and the wear-resistant paint losing workability is forbidden secondary to add water to stir to use again.
CN201410169540.2A 2014-04-25 2014-04-25 Nano wearproof pottery composite protective construction method Expired - Fee Related CN103924752B (en)

Priority Applications (1)

Application Number Priority Date Filing Date Title
CN201410169540.2A CN103924752B (en) 2014-04-25 2014-04-25 Nano wearproof pottery composite protective construction method

Applications Claiming Priority (1)

Application Number Priority Date Filing Date Title
CN201410169540.2A CN103924752B (en) 2014-04-25 2014-04-25 Nano wearproof pottery composite protective construction method

Publications (2)

Publication Number Publication Date
CN103924752A CN103924752A (en) 2014-07-16
CN103924752B true CN103924752B (en) 2016-02-03

Family

ID=51143130

Family Applications (1)

Application Number Title Priority Date Filing Date
CN201410169540.2A Expired - Fee Related CN103924752B (en) 2014-04-25 2014-04-25 Nano wearproof pottery composite protective construction method

Country Status (1)

Country Link
CN (1) CN103924752B (en)

Families Citing this family (3)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
CN105400430A (en) * 2015-12-14 2016-03-16 淮南东辰橡塑有限责任公司 Hydraulic bracket stand column protective sleeve for coal mine
CN116120767A (en) * 2023-01-01 2023-05-16 无锡远能耐火材料有限公司 A medium-quality waterproof and anti-corrosion coating and its construction technology
CN116478565A (en) * 2023-03-27 2023-07-25 合肥科德电力表面技术有限公司 High-temperature-resistant wear-resistant paint, denitration flue coating structure and construction process

Family Cites Families (6)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
JP2007092030A (en) * 2005-08-05 2007-04-12 Rohm & Haas Electronic Materials Llc Improved opaque coating
CN100418920C (en) * 2007-01-26 2008-09-17 牟元全 Wear-resistant ceramic coating
CN100427553C (en) * 2007-06-22 2008-10-22 洛阳鹏飞耐火耐磨材料有限公司 Wearable ceramic coat and preparation method thereof
JP6154102B2 (en) * 2011-05-09 2017-06-28 吉野石膏株式会社 Reaction-curing powder joint treatment composition
CN202074182U (en) * 2011-05-17 2011-12-14 赵宁 Wear-resistant ceramic coating with integral structure
CN202378331U (en) * 2011-12-26 2012-08-15 成都京龙科技有限公司 Ceramic wear-resistant coating protective plate

Also Published As

Publication number Publication date
CN103924752A (en) 2014-07-16

Similar Documents

Publication Publication Date Title
CN102146563B (en) Production process for intelligent temperature adjusting steel rail with laser cladding layer and heat insulation coating
CN102718454B (en) Exposed reinforcing steel bar rust-proof cement paste in building construction and processing method
CN101822936A (en) High-temperature scale anticorrosion construction method for desulfurization device of thermal power plant
CN102115884B (en) Preparation method of wear-resistant and corrosion-resistant composite coating
CN105176324A (en) Wear-resisting impact-resisting anti-corrosion coating layer and construction method thereof
CN102351491A (en) Concrete building anti-abrasion thin layer repairing material and repairing construction method
CN103397803A (en) Construction method using glass fiber reinforced plastics as inner cavity protective materials for steel and concrete chimney
CN103924752A (en) Nano wear-resisting ceramic composite protection construction method
CN108906554A (en) A kind of rolling stock coating layer structure and coating process
CN103937368B (en) A kind of anticorrosion antiwear patching material
CN107400417B (en) Special steel bar anti-corrosion paint for aerated concrete plate and production method thereof
CN108035247A (en) A kind of bridge on highway concrete structure anticollision barrier nanometer coating process
CN106883734B (en) A kind of application of resin ceramic material in the antiseptic project of wet desulphurization absorption tower
CN102690548A (en) A solvent-free epoxy acid-resistant anticorrosion putty coating used for smoke evacuation cooling tower
CN217621177U (en) A kind of cement counterweight
CN110130615B (en) Indoor composite floor based on phosphorus-magnesium material and self-leveling gypsum and its construction method
CN110714405A (en) Paving method of novel bicycle lane steel bridge deck paving layer structure
CN105130475B (en) A kind of low-temperature setting spray paint and its construction method
CN107337458A (en) A kind of special gunning refractory of coal injection pipe
CN105273456A (en) Porous wear-resisting ceramic and preparation method thereof
CN108751925A (en) A kind of roadmarking material and construction method based on phosphorus magnesium material
CN101811890A (en) Acid-resisting complex phase ceramic coating and preparation method thereof
CN208810511U (en) A kind of rolling stock coating layer structure
CN202378331U (en) Ceramic wear-resistant coating protective plate
CN102085512A (en) Method for spraying ceramic layer on metal surface

Legal Events

Date Code Title Description
C06 Publication
PB01 Publication
C10 Entry into substantive examination
SE01 Entry into force of request for substantive examination
C14 Grant of patent or utility model
GR01 Patent grant
CF01 Termination of patent right due to non-payment of annual fee
CF01 Termination of patent right due to non-payment of annual fee

Granted publication date: 20160203